Permafrost is warming at a global scale - Boris K. Biskaborn (Nature Portfolio, 2019)
Climate change strongly impacts regions in high latitudes and altitudes that store high amounts of carbon in yet frozen ground. Here the authors show that the consequence of these changes is global warming of permafrost at depths greater than 10 m in the Northern Hemisphere, in mountains, and in Antarctica.